The Implementation of Leadership Among Principals to Improve Teacher Discipline in Seruyan Regency - Ali Sobirin; Suryanto Suryanto; Didi Supriadi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop and test the effectiveness of the Among leadership model of school principals in improving teacher discipline in Seruyan Regency, Central Kalimantan. The Among leadership, based on Ki Hajar Dewantara's trilogy (Ing Ngarso Sung Tuladna, Ing Madya Mangun Karsa, Tut Wuri Handayani), was translated into five operational stages: role modeling, motivation, mentoring, evaluation, and follow-up. This study employed a research and development (RD) method with a product development model. The research subjects consisted of 168 participants, including 10 school principals and 158 teachers from 10 elementary and secondary schools spread across three representative sub-districts in Seruyan Regency, namely Seruyan Hilir Sub-district (urban), Seruyan Tengah Sub-district (peri-urban), and Seruyan Raya Sub-district (remote area). Subjects were selected using purposive sampling technique based on criteria of principals who had served for at least 2 years, schools with minimum B accreditation, and willingness to participate in the research. The data analysis techniques employed included both qualitative and quantitative data analysis. Qualitative data analysis followed the Miles and Huberman model consisting of three stages: data reduction, data display, and conclusion drawing/verification, complemented by source and method triangulation to ensure data credibility. Quantitative data analysis used descriptive statistics to calculate percentages and mean scores of teacher discipline indicators, as well as paired sample t-test to examine the significance of differences between pre- and post-implementation conditions of the Among leadership model. The results showed that the application of Among leadership significantly improved teacher discipline. The Teacher Discipline Index (TDI) increased from 76.58 before implementation to 87.15 after implementation, representing an increase of 13.80%. Based on indicators, the highest improvements occurred in punctuality entering class (19.85%) and learning administration (19.66%), followed by punctuality of attendance (13.74%), effective teaching hours (13.31%), and teacher attendance (4.82%). The paired sample t-test result showed t = 9.87 with a significance level of p 0.001, indicating a very significant difference between pre- and post-implementation conditions. Therefore, the Among leadership model is proven effective and recommended to be implemented as a guideline for fostering teacher discipline, particularly in areas with geographical and sociocultural characteristics similar to Seruyan Regency.